Utilization of splitting strips in fracture mechanics tests of quasi-brittle materials - Ince, Ragip (Springer, 2021)
In this study, utilizing the boundary collocation approach based on the generalized Westergaard formulation developed by Sanford, alternative splitting strips with various ratios of length/depth, L/h = 0.5, 0.75, 1.25, and 1.5, were first discussed for fracture mechanics of quasi-brittle materials for different load-distributed widths. By modifying Sanford's approach, some formulae calculating the tensile capacity of materials were subsequently proposed for strips without notches. To determine the simulating capacity of the split-tension strips on the fracture behavior of quasi-brittle materials, the formulas derived in this study were also applied to a popular fracture approach, the two-parameter model (TPM) in concrete fracture. As a result of the stress analysis based on this application, a square prismatic specimen type with edge crack was proposed to determine the fracture parameters of quasi-brittle materials. Subsequently, an experimental investigation on splitting cubes with edge cracks (L/h = 0.5) was performed. The analysis of this specimen based on TPM yielded viable and promising results.
Keywords: Boundary collocation method; Fracture mechanics; Green’ s function; Quasi-brittle materials; Splitting test